A novel ddPCR™ assay for eDNA detection and quantification of Greater Amberjack Seriola dumerilli and three congeners in US waters: challenges and application to fisheries independent surveys - P. Joana Dias; Ryan Lehman; Bryan L. Huerta-Beltrán; Ana Wheeler; Crystal L. Hightower; Jessica Heise; Theodore Switzer; Clint Rhode; J. Marcus Drymon; Lynne Stokes; Mark A. Albins; Sean Powers; et al. (PeerJ)
Background Four Seriola species support recreational and commercial fisheries along the U.S. Atlantic Ocean and the Gulf of Mexico, with the S. dumerili Gulf of Mexico stock being overfished for over three decades. The study presented here is part of a fisheries-independent project initiated to determine an absolute abundance of S. dumerili, to expand biological knowledge of the species and to develop novel tools for fisheries management. Environmental DNA (eDNA) tools aimed at the detection and quantification of target species are starting to emerge in support of marine fisheries surveys. Key to progressing the field is Droplet Digital™ PCR (ddPCR™), a highly sensitive technique with advanced multiplexing and direct quantification capabilities that can provide fisheries scientists with improved interpretation of eDNA data. Methods We developed and validated a novel tetraplex ddPCR™ assay able to detect and distinguish between S. dumerili, S. fasciata, S. rivoliana, and S. zonata from seawater eDNA samples. In order to groundtruth ddPCR™ data, and explore its capacity to provide abundance estimates, we compared ddPCR™ detections and quantifications to abundance data inferred from multiple camera (ROV, S-BRUV, chevron trap) and acoustic (VPS array) gears deployed during a fisheries research gear-calibration cruise. Results We demonstrated that with eDNA contamination controls and best practice protocols, it is viable to conduct eDNA research as part of a fisheries survey cruise. eDNA sampling was completed in less time than camera gears (15 min vs 2 h). Both eDNA and camera gears detected the presence of S. dumerili and S. rivoliana at both sites and all sampling days, but not S. fasciata and S. zonata. eDNA concentration data was higher for S. dumerili than S. rivoliana at both sites for all sampling days, in line with abundance patterns obtained from camera gears. The highest correlation (r = 0.97) was obtained between the measures of eDNA between gear deployments and ROV. Discussion Incorporating eDNA in fisheries surveys would not require additional days at sea and could improve precision in fish detection and abundance. eDNA can be a valuable complement to camera gears deployed in geographic areas or seasons with poor visibility conditions, where fish may be present but cannot be confidently identified to the species level. The high correlation obtained between ROV and eDNA data collected between gear deployments adds to a growing number of studies demonstrating the potential of eDNA as an indicator of abundance for fisheries stock assessments. Time-series data from a carefully designed eDNA survey, that estimates relative abundance, could be used as an index of relative abundance for the S. dumerili stock assessment. To achieve this, investment into follow-up studies with increased sample sizes and spatial and temporal replication would be necessary to allow for year-to-year comparisons and validate the robustness of the correlation observed.